Effects of the structural change on transaction costs between North America natural gas spot markets - Kannika Duangnate (2018)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Threshold cointegration between market pairs before and after the potential structural break associated with the shale gas revolution is examined. Pairwise transaction costs differ between the pre- and post-break periods. During the post-break period, five of seven pairwise transaction costs decrease, while the remaining two pair-wise transaction costs increase relative to the pre-break period. Alterations in natural gas flows as the result of the shale gas revolution partially explain the changes in transaction costs.